IMPLEMENTASI METODE 3T+1M PROGRAM TAHFIDH JUZ AMMA UNTUK MENINGKATKAN MOTIVASI MENGHAFAL PESERTA DIDIK DI SDN 2 TAWANGREJO LAMONGAN (PIONIR: JURNAL PENDIDIKAN, 2022)
This article examines the implementation of the 3T+1M method (Talqin, Tafahhum, Tikrar and Muroja'ah) in 5th grade students of SDN 2 Tawangrejo Lamongan which aims to increase memorization motivation in the Tahfidh juz amma program. The 3T+1M method is one method that is easy, effective and suitable to be implemented on students from grade 5 who are vulnerable between the ages of 10-11 years who are categorized as middle and late childhood. The method used in this research is a qualitative field research method or field research. Data analysis techniques through the stages of data reduction, data presentation and conclusions. The results of this study indicate that the steps for memorizing juz amma with the 3T+1M method are: 1) Students listen to letters read by educators, 2) Educators explain the contents of the letters read, 3) Students read repeatedly until students memorize them. 4) Students then repeat their memorization with the teacher. The determinants of the success of students in memorizing are psychological, emotional and intelligence factors.
Keywords: 3T 1M Method; Memorization Motivation; Tahfidh Juz 'Amma.